9-Year Trajectory of Depressive and Anxiety Symptoms in Community – the Hong Kong Mental Morbidity Survey Follow Up Studies - Linda CW Lam; Bob Z Huo; Owen NW Leung; Allen TC Lee; Eric YH Chen (BJPsych Open)
Aims: Depression and anxiety are common in every community. Appreciation of the long-term trajectories of these symptoms will inform more targeted interventions for reduction of disease burden. We evaluated the 7th and 9th year episode onset and remission rates of common mental disorders (CMD) in participants of the Hong Kong Mental Morbidity Survey (HKMMS) at baseline (2010–2023), who were reassessed at 7th and 9th years follow up.